Encapsulation of Compounds Biphenyls Into SBA-15: Synthesis of Composites for Application - Guntero, Vanina Alejandra (2018)
Two novel hybrid mesoporous material BVA-SBA and BEG-SBA were designed and synthesized by a process assisted by microwave. The nanoparticles were studied by UV-vis and fluorescence spectroscopy, elemental analysis, nitrogen adsorption-desorption, RMN and FTIR. The results obtained indicates the successful immobilization of BVA and BEG in the mesoporous composite. These systems present the possibility of activating the release of the organic molecules encapsulated into SBA-15, depending on the liquid medium in which the composite are suspended.